RADIOPROTECTIVE PROPERTIES OF ALLIUM SATIVUM (GARLIC) EXTRACT ON CULTURED HUMAN LYMPHOCYTES AGAINST ELECTRON BEAM RADIATION (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The radioprotective effects of naturally occurring compounds from herbs have been investigated in vitro and in vivo considering their ethnopharmacological role in prevention and treatment of cancer. Allium sativum supplementation in diet has been shown to be beneficial to cancer patients. The present study was designed to detect the radioprotective effect of garlic extract (GE) on cultured human peripheral blood lymphocytes. Garlic bulbs were extracted using ethanol and water separately followed by assays on antioxidant activities to assess the efficiency of radical scavenging capacity of various extracts. Lymphocytes were treated with different concentrations of GE for 2, 4, 6 and 24 hr periods. Cell survival was determined by tryphan blue dye exclusion assay, single strand DNA damage by alkaline comet assay and in vitro cytogenetic damages were evaluated by micronucleus assays. Ethanol boiled GE showed highest radical scavenging capacity and reducing property. Treatment of GE to lymphocytes before and after exposure to 4Gy of electron beam radiation (EBR) the percentage of tail DNA was reduced from 24.06±3.92 to 2.87±0.18. The elevated micronucleus formation in radiation control group (13.15±0.75) was significantly reduced in various concentrations of GE treated groups (10.35±0.44, 7.05±1.17, 6.42±0.47) respectively. Cells treated with GE at 10µg/mL showed maximum viability after exposure to EBR. Present investigations indicate that ethanol boiled GE shows good radiation protection at 10µg/mL concentration. However, increase in concentration above this dose though resulted in higher protection, increased cell toxicity was also noticed.